Review of the mechanism of infection induced cerebral small vessel disease - Song, Jiamei; Wang, Yiqin; Xie, Zhaoxia; Wei, Jiayi; Wang, Jue (Frontiers in Immunology, 2025)
Cerebral small vessel disease (CSVD) refers to a group of pathological syndromes that affect the brain’s microcirculation. These conditions involve damage to small arteries, arterioles, capillaries, venules, and small veins. Cerebrovascular risk factors, immunosenescence, and inflammatory responses contribute to the pathogenesis of cerebral small vessel disease. The global impact of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has drawn significant attention to chronic inflammation caused by infections. Research into the mechanisms by which infections induce CSVD has made continual advancements. It is imperative to reassess the importance of managing infections and the chronic inflammatory phase that follows, highlighting their critical role in the pathogenesis. Our focus encompasses SARS-CoV-2, Human Immunodeficiency Virus (HIV), Hepatitis C Virus (HCV), Zika Virus(ZIKV), Treponema pallidum, as well as the microbial communities within the gut and oral cavity. These pathogen infections and chronic inflammation can contribute to CSVD through mechanisms such as neuroinflammation, blood-brain barrier disruption, microthrombosis, and endothelial cell damage, thereby promoting the occurrence and progression of the disease. This highlights the need for detailed mechanistic research on CSVD associated with these pathogens. Furthermore, we hope that in the future, we will be able to devise targeted prevention and treatment strategies for CSVD based on the unique characteristics of the pathogenic mechanisms associated with various infections.